Can modern football match demands be translated into novel training and testing modes? - Bradley, P. S.; Di Mascio, M.; Mohr, M.; Fransson, D.; Wells, C.; Moreira, A.; Castellano, J.; Gomez, A.; Ade, J. D. (ASPETAR Sports Medicine Journal, 2018)
Association football is a complex sport with unpredictable activity patterns during matches. Players regularly transition between short multi-directional high-intensity efforts and longer periods of low-intensity activity. Time-motion analysis has been the data collection technique of choice to quantify the physical match performance of elite footballers. In the last 4 decades this technique has quantified the relative or absolute distance covered and time spent along a motion continuum of walking through to sprinting. This is accomplished with the aid of validated manual/computerised tracking or global/local positioning technology. Technological advances in wearables such as tri-axial accelerometers have enabled inertial indices to be progressively introduced alongside traditional time-motion techniques to provide more insight into metabolically taxing activities. This has surely progressed the understanding of the physiological, metabolic and mechanical demands of elite football match play; although more validation work should be conducted to compare inertial indices with physiological and metabolic measures.